Permasalahan Pemahaman Konsep Siswa pada Pelajaran Matematika Kelas 3 Semester 1 - Defi Prasasti; Fitri Maulida Awalina; Ulia Usawatun Hasana (MANAZHIM, 2020)
Mathematics education in elementary school is the beginning of a child's start to explore his ability to understand concepts in mathematics and the knowledge gained will greatly influence it at the next level of education. Learners in solving comparison questions, including concept errors which are wrong in presenting a form of comparison. The wrong principle that was made was wrong in using the principle of comparative dedication. While the operation error performed is in calculating the results of the comparison simplicity.